Demographics, aetiology and outcome of paediatric acute liver failure in Singapore - Fang Kuan Chiou; Veena Logarajah; Christopher Wen Wei Ho; Lynette Suk-Hui Goh; Sivaramakrishnan Venkatesh Karthik; Marion Margaret Aw; Kong Boo Phua (Singapore Medical Journal)
Introduction: The aetiology of paediatric acute liver failure (PALF) varies widely according to age, and geographic and socioeconomic factors. This study aimed to examine the epidemiology, aetiology and outcome of PALF in Singapore at a single centre. Methods: A retrospective review was performed of patients aged 0–18 years who were diagnosed with PALF from 2007 to 2019. PALF was defined by: absence of chronic liver disease; biochemical evidence of acute liver injury; and coagulopathy, non-correctible by vitamin K, defined as prothrombin time (PT) ≥20 seconds or international normalised ratio (INR) ≥2.0 regardless of hepatic encephalopathy (HE) or PT ≥15 seconds or INR ≥1.5 in the presence of HE. Results: 34 patients were included. Median age at diagnosis was 10 months (range 7 days to 156 months). The top three causes of PALF were indeterminate (41.2%), metabolic (26.5%) and infectious (26.5%) aetiologies. A metabolic disorder was the most frequent aetiology in infants <12 months (38.9%), whereas an indeterminate cause was the most common in children >12 months (50%). No cases of viral hepatitis A or B presenting with PALF were detected. Overall spontaneous recovery rate (survival without liver transplantation [LT]) was 38.2%, and overall mortality rate was 47.1%. Six patients underwent living-donor LT, and the post-transplant survival at one year was 83.3%. Conclusion: The aetiologic spectrum of PALF in Singapore is similar to that in developed Western countries, with indeterminate aetiology accounting for the majority. PALF is associated with poor overall survival; hence, timely LT for suitable candidates is critical to improve survival outcomes.